Study on conversion of vegetable oil deodorizer distillate to biodiesel using mesoporous oxo-phosphated sulfated zirconia - Pham, Phong Van; Nguyen, Hong Khanh Dieu (Vietnam Journal of Science and Technology, 2017)
Mesoporous oxo - phosphated sulfated zirconia (m-PSZ) were applied for converting vegetable oil deodorizer distillate to biodiesel in one-step reaction. The catalyst possessed mesopores, high surface area and strong acid sites while the feedstock contained mainly free fatty acids. Many investigations were established for finding the most suitable conditions of the biodiesel synthesis process